Propofol Inhibits Microglial Activation via miR-106b/Pi3k/Akt Axis - Liu, Jianhui; Ai, Pu; Sun, Yiyan; Yang, Xiaoyu; Li, Chunhong; Liu, Yihan; Xia, Xiaohuan; Zheng, Jialin C. (Frontiers in Cellular Neuroscience, 2021)
Propofol is an established intravenous anesthetic agent with potential neuroprotective effects. In this study, we investigated the roles and the underlying mechanisms of propofol in inhibiting the pro-inflammatory responses of microglia. Propofol significantly reduced the mRNA levels of Tnf, Nos2, and NF-κB pathway related genes Ticam1, Myd88, Irf3, and Nfkb1 in LPS-treated primary microglia. After screening the miRNA profiles in microglia under LPS and propofol treatment conditions, we found propofol abrogated the LPS-induced misexpression of miRNAs including miR-106b, miR-124, miR-185, and miR-9. Perturbation of function approaches suggested miR-106b as the core miRNA that mediated the anti-inflammatory effects of propofol on microglial activation. RNA-seq analysis further identified Pi3k/Akt signaling as one of the most affected pathways after miR-106b perturbation of function. The treatment of Pi3k/Akt signaling agonist 740Y-P elevated miR-106b-reduced Akt phosphorylation and abolished the inhibitory effects of miR-106b on the pro-inflammatory responses of microglia. Our results suggest propofol inhibits microglial activation via miR-106b/Pi3k/Akt axis, shedding light on a novel molecular mechanism of propofol-mediated immunomodulatory effects and implying propofol as potential therapeutics for treating neuroinflammation-related neurodegenerative diseases.